Comparative Study of Tru-Cut Biopsy and FNAC in A Clinically Palpable Breast Lump (Ibrahim Cardiac Medical Journal, 2022)
Background & Objective: Fine-needle aspiration cytology (FNAC) is frequently used to evaluate a breast lump, for it is safe, reliable, and time saving outdoor procedure for evaluation of breast lumps. However, in recent times, the diagnosis of breast lesions has mostly become dependent on Tru-cut biopsies with a gradual reduction in the rate of performing fine-needle aspiration cytology (FNAC). The present study was undertaken to compare the diagnostic accuracy of Tru-cut Biopsy and Fine Needle Aspiration Cytology (FNAC) in the evaluation of a clinically palpable breast lump.Methods: This cross-sectional study was conducted in the in Department of Surgery, Rajshahi Medical College & Hospital, Rajshahi, Bangladesh over a period of one year from July 2019 to June 2020. A total of 60 women with clinically palpable breast lumps were consecutively included in the study. All patients underwent FNAC and Tru-cut Biopsy to make a provisional (clinical) diagnosis of breast lump followed by histopathology of the excision biopsy taken during surgery to confirm the diagnosis. The diagnostic accuracies (sensitivity, specificity, positive and negative predictive values) of the two diagnostic modalities (FNAC and Tr-cut Biopsy) were then judged by comparing them with the histopathological diagnosis of the excision biopsy.Result: In the present study majority (86.7%) of the lesions was malignant in terms of histopathology with almost all being infiltrating carcinoma (98%). Only 8(13.3%) cases were benign breast lesions and all of them were fibroadenoma. While Tru-cut or Core-needle biopsy (CNB) diagnosed 85% of the lesions as malignant, FNAC diagnosed 65% of lesions as malignant. The sensitivity of CNB was observed to be 98.1% and its specificity was 100%. In contrast, the sensitivity of FNAC was much lower (65%), although its specificity was comparable to that of CNB (100%). While the overall diagnostic accuracy of CNB was 98.3%, that of FNAC was 78.3%. The test of agreement between Tru-cut biopsy and FNAC using kappa-statistics showed that the two diagnostic modalities had moderate agreement in differentiating malignant breast tumours from the benign ones (k-value = 0.494, p < 0.001).Conclusion: The study concluded that Tru-cut biopsy and FNAC both are hundred percent specific in excluding a benign breast lesion. However, the sensitivity of FNAC is much lower compared to that of CNB with overall diagnostic accuracy of Tru-cut biopsy being much higher than FNAC.Ibrahim Card Med J 2021; 11 (1): 21-27